(untitled) (Research, Society and Development, 2020)
Outpatient absenteeism can be conceptualized as the absence of the user to the appointment and/or examination previously scheduled or when the health institution is communicated, however without allowing the communication of a new user to the consultation and/or examination not performed. This scenario supported the objective of measuring the economic cost of outpatient absenteeism of patients from the Psychosocial Care Outpatient Clinic of the University Hospital of Santa Maria (AAPS/HUSM), in the period 2015-2017. This purpose was met by using the cost per absorption method. In addition, interviews were conducted with agents participating in the appointment scheduling and execution process in order to obtain their perception of outpatient absenteeism and its economic repercussions. In terms of results, from the allocation of these costs, we obtained the amount related to the economic losses of absenteeism, which, on average, was R396.000,00 per year in the three years analyzed for the AAPS/HUSM. Regarding the unit cost per consultation, the results showed that the average cost per scheduled patient was R202.92 while the average cost per patient attended was R252.95. As determinants of absenteeism, it was evidenced mainly those related to users, especially forgetfulness, lack of awareness and neglect of the user. As for the control of absenteeism as its repercussions on the institution’s revenues, although the monitoring is being performed through reports, the informational level is asymmetric among the agents involved in the scheduling and execution process.